Prevalence and Incidence of Hepatitis C Virus in Hemodialysis Patients in British Columbia: Follow-up after a Possible Breach in Hemodialysis Machines - Andrew W Tu; Jane A Buxton; Mandy Whitlock; Ognjenka Djurdjev; Mei Chong; Mel Krajden; Monica Beaulieu; Adeera Levin (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: A possible breach of the transducer protector in specific dialysis machines was reported in June 2004 in British Columbia (BC), which led to testing of hemodialysis patients for hepatitis C virus (HCV), hepatitis B virus (HBV) and HIV. This testing provided an opportunity to examine HCV incidence, prevalence and coinfection with HBV and HIV, and to compare anti-HCV and HCV polymerase chain reaction (PCR).